Public Perceptions of Robotic versus Laparoscopic Surgery in India: A Knowledge, Attitudes, and Perceptions (KAP) Survey (Indian Journal of Public Health Research & Development, 2026)
Background:Minimally invasive surgery (MIS) has transformed surgical care by reducing postoperative pain, complications, and recovery time. Laparoscopic surgery and robotic-assisted surgery (RAS) are the two principal MIS approaches; however, public understanding of their differences remains limited. This study assessed the knowledge, attitudes, and perceptions (KAP) of the Indian public toward laparoscopic and robotic surgery.Methods:A cross-sectional, questionnaire-based survey was conducted among Indian adults (≥18 years) who were patients or caregivers involved in surgical decision-making. A previously published questionnaire adapted from Brar et al. (2024) was used. The 20-item online survey assessed demographics, knowledge, perceptions of safety and cost, and surgical preferences. Healthcare professionals were excluded. Descriptive statistics were calculated using SPSS.Results:Forty-six respondents completed the survey (51.1% male; 48.9% female). Doctors were the primary source of information for laparoscopic (61.0%) and robotic surgery (43.5%). Most participants (60.9%) perceived both approaches as equally safe, while 28.3% believed robotic surgery offered better outcomes. Robotic surgery was perceived as more expensive by 80.4% of respondents. Mean trust scores were high for both techniques on a five-point Likert scale (laparoscopic: 4.26 ± 0.85; robotic: 4.08 ± 0.94). Surgical decisions were mainly influenced by physicians (60.9%), followed by self-education (32.6%).Conclusion:Respondents demonstrated high awareness and trust in minimally invasive surgery. Both laparoscopic and robotic approaches were perceived as safe and effective; however, robotic surgery was consistently viewed as more expensive. Surgical decision-making remained predominantly doctor-led, with an emerging trend toward patient self-education and shared decision-making.
Keywords: Robotic surgery; Laparoscopic surgery; Public perception; Knowledge, attitudes and practices (KAP)